ANALYSIS OF STUDENTS’ ANSWERS TOWARD SOLVING PISA LIKE TEST WITH INDONESIAN CONTEXTS IN PHYSICS EDUCATION OF FACULTY TEACHER TRAINING AND EDUCATION SRIWIJAYA UNIVERSITY - SUSANTI, RAHMI; ISMET, ISMET; HARTONO, HARTONO
The aim of research is to describe students’ answers toward PISA like tests withIndonesian contexts. The research involved 35 students that consisted of 11 groups.The total of Pisa like tests are five essay items.. The result of research showed that:1) 54.54% of students’s answers related to temperature and dangerous elements involcano dust toward crop plants; 2) 36% of students’ answers related to waves andfrequencies to solve question: effects of earthquake that caused differences of leveldistroys. 3) 27% of students’ answers related to kinds of gases that produced in thevolcano that reacted with rain water to solve question: effects of earthquake towardacid rain; 4) 27.3% of students’ answers related to lack of diversity and poluttion tosolve question: effect of vegetation destroys caused of smoke; and 5) only 18.18%of students’ answers related to abilities of CaCl2 solution to bond smoke to solvequestion: function of CaCl2 to reduce smoke. The research was concluded that67.28% of test items were not answered well based on answer keys.